2018
DOI: 10.1111/1468-2427.12654
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Urban Planning in The ‘Green Republic’: Tourism Development and the Nature–Infrastructure Paradox in Costa Rica

Abstract: This article examines coastal urban planning in Costa Rica vis‐à‐vis the country's values in the areas of sustainable tourism and community development, focusing on the city of Jacó. I argue that an anti‐urban tourism development strategy, swift coastal urban development and weak planning have nurtured a nature–infrastructure paradox: when people are brought closer to nature without proper urban and governmental infrastructure, this causes social and environmental damage. To assess this paradox and understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 67 publications
0
14
0
2
Order By: Relevance
“…The biogeophysical ecosystem has been impacted by the loss of polar ice, increasing sea water quality, desert extension, intensified rain and floods, climate change, disappearance of flora and fauna, and migration of fauna and pests (Ai et al, 2008;Williams, 2014;Brochier & Ramieri, 2001). Impact on the community's socioeconomic activities: destruction of the coast and coastal towns, disruption of path, port, and airport infrastructure functions (Chang, 2016;Deshmukh, 2010;Petterson et al, 2006;Irazábal, 2018;Zsamboky et al, 2011). Disruption of human settlements and agricultural production Risk of cancer and disease outbreaks was increased…”
Section: Global Environmental Causes and Impactsmentioning
confidence: 99%
“…The biogeophysical ecosystem has been impacted by the loss of polar ice, increasing sea water quality, desert extension, intensified rain and floods, climate change, disappearance of flora and fauna, and migration of fauna and pests (Ai et al, 2008;Williams, 2014;Brochier & Ramieri, 2001). Impact on the community's socioeconomic activities: destruction of the coast and coastal towns, disruption of path, port, and airport infrastructure functions (Chang, 2016;Deshmukh, 2010;Petterson et al, 2006;Irazábal, 2018;Zsamboky et al, 2011). Disruption of human settlements and agricultural production Risk of cancer and disease outbreaks was increased…”
Section: Global Environmental Causes and Impactsmentioning
confidence: 99%
“…There is a growing body of knowledge related to the influence of the destination image on tourist behavior [18,[50][51][52]. It has been shown that destinations with strong positive images are more likely to be considered and chosen in the travel decision process [53], even if the destination image influences more than just the destination selection process, such as general tourist behaviors. Qu et al's [24] study showed that there are two key elements of tourist behavior that merit further analysis, namely intentions to revisit and recommend the destination.…”
Section: Tourist Behavioral Intentionsmentioning
confidence: 99%
“…Cater [19] critiqued eco-tourism in developing countries, arguing that without adequate understanding of environmental factors and without careful planning and management, it was likely to produce unsustainable outcomes. Irazábal [20] argued that bringing people to nature without appropriate planning and infrastructure would cause more harm than good to the natural resources. Lindberg and McKercher [21] argued that as eco-tourism ventures reached a stage of maturity and popularity, they inevitably degrade environments, and concluded that the promised benefits of eco-tourism are not actually in evidence.…”
Section: Criticism Of Eco-tourismmentioning
confidence: 99%